Large and Influential: Firm Size and Governments' Corporate Tax Rate Choice - Nadine Riedel; Martin Simmler (Center for Economic Studies and ifo Institute (CESifo), 2018)
Theory suggests that large firms are more likely to engage in lobbying behaviour and are geographically more mobile than smaller entities. Conditional on jurisdiction size, policy choices are thus predicted to depend on the shape of a jurisdiction's firm size distribution, with more business-oriented policies being enacted if jurisdictions host large firms. The paper empirically tests this prediction using local business taxation in Germany as a testing ground. Exploiting rich and exogenous variation in localities' firm size structures, we find evidence for an inverse relationship between the size of hosted entities and communities' local business tax choices. The effect is statistically significant and quantitatively relevant, suggesting that the rising importance of large businesses may trigger shifts towards a more business-friendly design of (tax) policies.
Keywords: H20; H70; 330; firm size; corporation tax; political economy